Stability and Feasibility of Dried Blood Spots for Hepatitis E Virus Serology in a Rural Setting - Joakim Øverbø; Asma Aziz; K. Zaman; Cathinka Halle Julin; Firdausi Qadri; Kathrine Stene-Johansen; Rajib Biswas; Shaumik Islam; Taufiqur Rahman Bhuiyan; Warda Haque; Synne Sandbu; Jennifer L Dembinski; et al. (Viruses, 2022)
Hepatitis E virus (HEV) is the most common cause of acute viral hepatitis worldwide. In many low-income countries it causes large outbreaks and disproportionally affects pregnant women and their offspring. Surveillance studies to find effective preventive interventions are needed but are hampered by the lack of funding and infrastructure. Dried blood spots (DBS) offer an easier and more robust way to collect, transport, and store blood samples compared to plasma/serum samples, and could ease some of the barriers for such studies. In this study we optimize an HEV IgG ELISA for DBS samples and validate it on 300 paired DBS and plasma samples collected in rural areas of Bangladesh from participants in a HEV vaccine study. We demonstrate that HEV IgG in blood stored as DBS is stable for two months at up to 40 °C, and for five freeze-thaw cycles. The specificity was 97% and the overall sensitivity of the DBS assay was 81%. The sensitivity was higher in samples from vaccinated participants (100%) compared to previously infected participants (59%), reflecting a positive correlation between IgG titer and sensitivity. We found a strong correlation between DBS and plasma samples with an r2 of 0.90, but with a higher degree of difference between individual paired samples. Our study shows that DBS offers a stable alternative to plasma/serum for HEV IgG measurements and can facilitate serological studies, particularly in resource limited areas.